Scoping Review: Faktor Sosial Budaya Terkait Pemberian Asi Eksklusif Di Indonesia - Izzatun Nidaa; Tri Krianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
Mother's milk is the best food for babies. Exclusive breastfeeding for six months provides health benefits for babies and their future. According to WHO, almost 2 out of 3 babies are not exclusively breastfed. In Indonesia, based on data from the Ministry of Health's 2020 Performance Report, the achievement of exclusive breastfeeding is only 66.1%. Indonesia is an archipelagic country that has various ethnic groups and cultures. The health condition of the people in Indonesia cannot be separated from the existing socio-cultural factors. The purpose of this literature review is to determine the socio-cultural factors associated with exclusive breastfeeding in Indonesia. Articles are searched by using Google scholar with the keywords “exclusive breastfeeding; socio-cultural” and “exclusive breastfeeding; social; culture; tradition; belief; myth” in the last five years of publication period, since 2017 to 2022. From the final selection, 12 articles were selected, consist of nine quantitative research methods articles and two qualitative research methods articles. From these articles, it is found that there are socio-cultural factors related to exclusive breastfeeding in Indonesia. These factors include belief in certain myths, traditions, support from husband/mother/mother in-law/family, support from health workers, mother's education level, mother's level of knowledge, mother's employment status, and income level. It is necessary to do a health promotion strategy with socio-cultural approach to increase the coverage of exclusive breastfeeding in Indonesia.